2001
DOI: 10.1086/322012
|View full text |Cite
|
Sign up to set email alerts
|

Association of Severe Malaria with a SpecificPlasmodium falciparumGenotype in French Guiana

Abstract: Why severe Plasmodium falciparum malaria occurs in only a small percentage of patients is unclear. The possibility that specific parasite characteristics contribute to severity has been investigated in French Guiana, a hypoendemic area, where parasite diversity is low and all patients with severe cases are referred to a single intensive care unit. Parasite genotyping in geographically and temporally matched patients with mild and severe disease showed that the association of a specific msp-1 allele (B-K1) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
82
1
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(93 citation statements)
references
References 12 publications
6
82
1
4
Order By: Relevance
“…For example, in French Guiana, it has been demonstrated that a specific MSP-1 allele (B-K1) bearing a specific variant gene (var-D) has been linked to severe malaria. 33 In Dienga, a village situated in southeastern Gabon approximately 200 km from Franceville where the present study was carried out, the K1 and Mad20 families of MSP-1 were predominantly found in symptomatic individuals compared to asymptomatics. 23 By contrast, in Nigeria it has been shown that the presence of the K1 and MAD20 alleles was significantly associated with asymptomatic malaria, and consequently, a reduced risk of developing the symptomatic disease.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…For example, in French Guiana, it has been demonstrated that a specific MSP-1 allele (B-K1) bearing a specific variant gene (var-D) has been linked to severe malaria. 33 In Dienga, a village situated in southeastern Gabon approximately 200 km from Franceville where the present study was carried out, the K1 and Mad20 families of MSP-1 were predominantly found in symptomatic individuals compared to asymptomatics. 23 By contrast, in Nigeria it has been shown that the presence of the K1 and MAD20 alleles was significantly associated with asymptomatic malaria, and consequently, a reduced risk of developing the symptomatic disease.…”
Section: Discussionmentioning
confidence: 81%
“…This result confirmed previous data reported elsewhere 2 and reinforces the conclusion that coma is the only manifestation caused by cytoadhesion of PRBC to the brain vascular endothelium via variant surface antigen. 43 Indeed, it has been documented that severe malaria is associated with expression of the variant surface antigen group A, [44][45][46] group B, 47 groups A or B/A, 48 groups A and B, 49 and group D. 33 Moreover, the postmortem analysis of the brain revealed that all coma cases did not have sequestered parasites in cerebral capillaries. 50 There is also evidence suggesting that severe malaria is associated with expression of PfEMP1 variants that do not bind to CD36.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, another recent study by the Rogerson's group suggested that the dominant clones sequestered in deep organ during severe malaria are usually the same as those in peripheral circulation (Dembo et al, 2006), which supports continued experimental work using circulating parasites. Several studies have used merozoites surface proteins (msp-1 and/or msp-2) polymorphism to describe circulating parasite populations and some authors reported the association of particular genotypes with severity of malaria attack (Ariey et al, 2001;Mockenhaupt et al, 2003;Ranjit et al, 2005;Farooq et al, 2006). However, these associations were described as possibly restricted to geographical areas.…”
Section: Discussionmentioning
confidence: 99%
“…We used a set of nine putatively neutral microsatellite markers, instead of surface antigen genes under strong selection pressure (1,4,16,21), to compare the genetic backgrounds of sympatric isolates from patients with cerebral and uncomplicated malaria. We tested the hypothesis that parasites causing cerebral malaria were more genetically related than expected by chance, instead of looking for associations between particular genotypes or antigenic variants and morbidity.…”
mentioning
confidence: 99%